LOCAL AND NEAR EARTHQUAKES IN GREATER SOCHI AREA, RUSSIAN BLACK-SEA COAST - Burmin V.Y. (My University, 1999)
This paper presents the results of seismological observations carried out in the greater Sochi area using a network of self-contained seismic stations to record low-magnitude seismicity during the period November 1995 to February 1996. The magnitude-frequency relations for two magnitude ranges, -1.0 to 1.0 and 2.5 to 5.5, are compared. The resulting plots for these two ranges turned out to be almost identical.